Synthesis of CaO-MgO Catalyst from Dolomite via Dissolution and Precipitation Processes - Amelia Salsabilla Cantika; Moh. Rizal Febriyanto; Ketut Sumada; Ardika Nurmawati; Caecilia Pujiastuti; Erwan Adi Saputro (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Dolomite is an abundant carbonate mineral containing calcium and magnesium compounds that can serve as a precursor for heterogeneous catalyst synthesis. This study investigated the effects of NaOH volume (90-170 mL) and dehydration temperature (300-700°C) on the synthesis and physicochemical properties of calcium-magnesium-based materials prepared via a dissolution-precipitation method, which was selected over conventional calcination because it enables systematic control of the precipitation process through adjustment of the NaOH volume. XRF analysis showed that the raw dolomite contained 88.81% CaO and 9.70% MgO. Two-way ANOVA confirmed that NaOH volume, dehydration temperature, and their interaction significantly affected catalyst basicity (p < 0.001), with the highest value (1.960 mmol/g) obtained at 150 mL NaOH and 500°C. SEM analysis of catalysts with low, medium, and high basicity revealed increasingly well-developed and uniformly distributed particle morphologies toward the optimum condition, while EDX identified calcium, magnesium, and oxygen as the predominant elements. BET characterization of the material exhibiting the highest basicity showed a specific surface area of 126.585 m2/g and an average pore diameter of 21.545 nm. These findings demonstrate that NaOH volume and dehydration temperature play important roles in tailoring the physicochemical properties of the catalyst materials. The optimized synthesis condition provides useful guidance for preparing calcium-magnesium-based materials with high basicity and favorable textural properties and serves as a foundation for future phase identification and catalytic performance evaluation. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action